PEMANFAATAN MEDIA INTERAKTIF KAHOOT DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Saputra, Ariya; Rila Melyana Fitri; Dedi Romli Triputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the utilization of Kahoot interactive media in improving student activeness and learning outcomes in elementary schools. This study employed a qualitative approach using the literature review method by analyzing various relevant scientific articles related to the use of Kahoot in learning activities. The data sources were obtained from national and international journals discussing interactive learning media, gamification, student activeness, and learning outcomes at the elementary school level. The results of the study indicate that the use of Kahoot as an interactive learning medium can increase student participation, enthusiasm, motivation, and engagement during the learning process. In addition, features such as quizzes, scores, rankings, and instant feedback contribute positively to improving student learning outcomes. The implementation of Kahoot also supports a more active, enjoyable, and student-centered learning environment. Therefore, Kahoot can be used as an innovative interactive learning medium to support the improvement of student activeness and learning outcomes in elementary schools